(untitled) (Current Horticulture, 2024)
Vegetables are an integral component of horticulture sector, praying a pivotal role in the tapestry of Indian agriculture. Their substantial contributions extend to enhancing global food security and nutritional well-being. During 2021-22, India produced 204.84 million tonnes of vegetables, covering the area of 11.35 million hectares, with a fresh vegetable export value worth 865.24 USD millions. The AICRP on Vegetable Crops has forged a national network to test vegetable technologies in India. In the past five decades, 587 vegetable varieties, 442 production technologies, and 42 protection technologies have been developed through AICRP. The use of molecular markers has been proven promising in several vegetable crops, however only limited example of improvements are available from India. Through genetic engineering several biotic and abiotic stress resistant lines are developed. The genome editing has opened a new avenue in development of improved lines, however it is just gaining momentum in vegetable research in India.